1995
DOI: 10.1002/syn.890200307
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural correlates of haloperidol‐induced oral dyskinesias in rat striatum

Abstract: Neuroleptics given chronically to rats induce behavioral sequelae which mimic tardive dyskinesia in some respects. The intent of this study was to investigate the ultrastructural correlates of oral dyskinesias (vacuous chewing movements [VCMs]), induced by chronic haloperidol treatment. After 6 months of treatment, rats were divided into low or high VCM groups. Rats in the high VCM group were either sacrificed on drug or were withdrawn from drug for 4 weeks. Ultrastructural analyses of the striatum indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 49 publications
11
61
6
Order By: Relevance
“…This disruption is believed to produce a number of compensatory changes, including increased striatal blood flow as well as activation, regeneration, hypertrophy and change in the number of striatal synapses (Muller and Seeman 1977;Benes et al 1983Benes et al , 1985Meshul and Casey 1989;Meshul et al 1994;Roberts et al 1995). An overriding question, however, is how striatal volume changes may affect either the course of schizophrenia or the efficacy of the different antipsychotic agents.…”
Section: Discussionmentioning
confidence: 99%
“…This disruption is believed to produce a number of compensatory changes, including increased striatal blood flow as well as activation, regeneration, hypertrophy and change in the number of striatal synapses (Muller and Seeman 1977;Benes et al 1983Benes et al , 1985Meshul and Casey 1989;Meshul et al 1994;Roberts et al 1995). An overriding question, however, is how striatal volume changes may affect either the course of schizophrenia or the efficacy of the different antipsychotic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate-like synapses are more numerous in SZ-Off and are decreased in number with successful treatment and with antipsychotic medication in rats (Roberts et al, 1995), suggesting that antipsychotic medication decreases glutamatergic tone, at least in striatum. Our exploratory finding of elevated vGLUT2 (indicative of increased subcortical glutamate release) (Raju et al, 2006) in SZ-Off, and not SZ-On, subjects are consistent with previous findings of medicationinduced normalization of glutamate release in other brain regions.…”
Section: Treatment Statusmentioning
confidence: 99%
“…However, we cannot determine if other striatal neuron tic density in the striatum of rats treated for 6 months with ෂ1.5 mg kg −1 day −1 haloperidol; indeed there were populations show a similar change, since their smaller size and lower level of synaptophysin expression make minor decreases in some animals. 27 The different durations and dosages of treatment in these studies may cellular quantitation problematic. Hence we have not speculated upon the significance which synaptic plasexplain the divergence of results.…”
Section: -57mentioning
confidence: 99%
“…4 For example, brain regions differmicroscopy data. [19][20][21][22][23][24][25][26][27][28] entially activated by typical and atypical antipsyMost studies of antipsychotic drug effects on gene chotics have been identified using oncogene expression expression have been limited to acute or subchronic as a marker, 5,6 and mRNAs encoding vesicle-associated treatment. Longer-term studies are also necessary since proteins have been used to localise neuronal and synprolonged or late-onset changes in gene expression may contribute to the delayed therapeutic benefits and side-effects of antipsychotics.…”
Section: Introductionmentioning
confidence: 99%